Peningkatan Pengetahuan dan Pencegahan Infeksi Pada Organ Reproduksi - Nafi'ah, Fadila Nurun; Tinartayu, Seshy; Kurniawan, Muhammad; An, Alfun Dhiya (Lembaga Peneliian dan Pengabdian Masyarakat (LPPM) Universitas Islam Madura (UIM), 2024)
The low level of knowledge regarding the prevention of infection in reproductive organs was a major concern in this community service activity. Lack of health socialization due to location and internet access was also a major factor in the problem. Thus, the purpose of this community service activity was to increase knowledge and prevent infection in the reproductive organs. This service activity was carried out in one of the residents' houses in Krambilsawit, Saptosari District, Gunung Kidul, D.I. Yogyakarta in February 2022. Participants consisted of 21 people and the activities carried out by providing material, question and answer, and pretest and posttest. Based on these activities, participants' knowledge about reproductive health was able to increase as indicated by the increased post-test scores at the end of the activity. It was hoped that this activity can be a solution and one of the initial actions to increase knowledge and reproductive health and can be passed on to the surrounding community.